2021
DOI: 10.3390/nu13051530
|View full text |Cite
|
Sign up to set email alerts
|

Intracortical and Intercortical Motor Disinhibition to Transcranial Magnetic Stimulation in Newly Diagnosed Celiac Disease Patients

Abstract: Background: Celiac disease (CD) may present or be complicated by neurological and neuropsychiatric manifestations. Transcranial magnetic stimulation (TMS) probes brain excitability non-invasively, also preclinically. We previously demonstrated an intracortical motor disinhibition and hyperfacilitation in de novo CD patients, which revert back after a long-term gluten-free diet (GFD). In this cross-sectional study, we explored the interhemispheric excitability by transcallosal inhibition, which has never been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…GFD ( Bella et al, 2015 ; Pennisi et al, 2017b ). Overall, these studies suggest a global pattern of intracortical and intercortical “hyperexcitable celiac brain,” which partially recovers with a long lasting GFD ( Lanza et al, 2018 , 2021 ; Fisicaro et al, 2021 ). Translationally, this hyperexcitability to TMS may represent the neurophysiological correlate of the hyperdynamic circulation to TCD, although, at this stage, an association only and not a causal or reciprocal effect can be postulated.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…GFD ( Bella et al, 2015 ; Pennisi et al, 2017b ). Overall, these studies suggest a global pattern of intracortical and intercortical “hyperexcitable celiac brain,” which partially recovers with a long lasting GFD ( Lanza et al, 2018 , 2021 ; Fisicaro et al, 2021 ). Translationally, this hyperexcitability to TMS may represent the neurophysiological correlate of the hyperdynamic circulation to TCD, although, at this stage, an association only and not a causal or reciprocal effect can be postulated.…”
Section: Discussionmentioning
confidence: 85%
“…In this scenario, transcranial magnetic stimulation (TMS), an electrophysiological technique that may non-invasively assess and monitor different neurological and neuropsychiatric disorders (Cantone et al, 2020(Cantone et al, , 2021Fisicaro et al, 2020;Di Lazzaro et al, 2021), even those without clear clinical manifestations (Lanza et al, 2020a,b), has been recently applied to CD patients, both at diagnosis (Pennisi et al, 2014;Lanza et al, 2021) and after a short-or long-term GFD (Bella et al, 2015;Pennisi et al, 2017b). Overall, these studies suggest a global pattern of intracortical and intercortical "hyperexcitable celiac brain, " which partially recovers with a long lasting GFD (Lanza et al, 2018(Lanza et al, , 2021Fisicaro et al, 2021). Translationally, this hyperexcitability to TMS may represent the neurophysiological correlate of the hyperdynamic circulation to TCD, although, at this stage, an association only and not a causal or reciprocal effect can be postulated.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…However, some excitatory changes persisted, likely indicating a synaptic intracortical rearrangement of the “celiac brain”, mostly involving the glutamate-mediated interneurons [ 52 ]. Recently, the interhemispheric excitability by the transcallosal inhibition was evaluated, as reflected by the duration and latency of the ipsilateral silent period (iSP) to TMS, in a sample of newly diagnosed CD patients [ 53 ]. We found that iSP was significantly shorter in patients than controls, with a positive correlation between MoCA score and iSP duration, suggesting an interhemispheric motor disinhibition and supporting the involvement of GABA [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the interhemispheric excitability by the transcallosal inhibition was evaluated, as reflected by the duration and latency of the ipsilateral silent period (iSP) to TMS, in a sample of newly diagnosed CD patients [ 53 ]. We found that iSP was significantly shorter in patients than controls, with a positive correlation between MoCA score and iSP duration, suggesting an interhemispheric motor disinhibition and supporting the involvement of GABA [ 53 ]. Taken together, these results support the interplay between GABAergic and glutamatergic circuits previously explored by using the paired-pulse TMS paradigm [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical treatment of schizophrenia requires comprehensive treatment to control schizophrenic symptoms, reduce the impact of schizophrenia, delay disease progression, and improve the long-term quality of life of patients as the goal of treatment [8]. The clinical treatment of schizophrenia is based on antipsychotic medication, but because of the slow progression of schizophrenia and the lack of an effective cure, patients often have to take medication for a long time, so the side effects of the medication cannot be ignored [9]. The side effects of long-term anti-schizophrenia medication can cause insulin antagonism, adrenaline antagonism, cardiac arrhythmia, and other adverse reactions and can easily affect the balance of glucose and lipid metabolism, causing patients to have abnormal glucose and cholesterol metabolism indicators.…”
Section: The Need For Tms Technology In the Treatment Of Schizophreniamentioning
confidence: 99%